1988
DOI: 10.1590/1809-43921988182374
|View full text |Cite
|
Sign up to set email alerts
|

Migração circadiana em cinco espécies de psitacídeos em Parintins - AM

Abstract: ) 0 comportamento de migração circadiana em PsitacTdeos tem sido relatado por diferentes autores (Forshaw, 1966; Forshaw, 1973;Sick et al . , 1979; Sick, 198**, 1985 Descrição da áreaTrata-se de uma ilha pequena com cerca de 5 hectares. Possui um solo excessivarner^ te arenoso e pobre, resultado das lavagens causadas pelo regime de cheias e vazantes do rio Uaicurapá. A vegetação nela ocorrente está sujeita a essas variações sazona i s do n_f vel do rio, caracterizando uma área de "mata de igapó estacionai" (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Our finding that the majority of parrots leave the roost site before sunrise is in agreement with the results of Rocha et al (1988) for a mixed roost of five parrot species leaving to spend the daylight hours in Terra firme forest. However, our data contrast with those of Harms and Eberhard (2003), who found that Aratinga pertinax individuals left the roost site after sunrise.…”
Section: Arrival Of Parrots At the Roosting Site And Abiotic Factorssupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that the majority of parrots leave the roost site before sunrise is in agreement with the results of Rocha et al (1988) for a mixed roost of five parrot species leaving to spend the daylight hours in Terra firme forest. However, our data contrast with those of Harms and Eberhard (2003), who found that Aratinga pertinax individuals left the roost site after sunrise.…”
Section: Arrival Of Parrots At the Roosting Site And Abiotic Factorssupporting
confidence: 91%
“…However, we have no data of relevance to this hypothesis. The return from the roost site to Terra firme forest is presumably related to inadequate food supplies for the high number of parrots at the roost (Rocha et al 1988).…”
Section: Arrival Of Parrots At the Roosting Site And Abiotic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most Psittacids are gregarious (JUNIPER; PARR, 1998), living in flocks formed by two or even hundreds of specimens (ROCHA et al, 1988).…”
Section: Introductionmentioning
confidence: 99%